25. ANEMIA IN PEDIATRIC PATIENTS WITH CHRONIC KIDNEY DISEASE STAGES G3A-5: PREVALENCE AND ASSOCIATED FACTORS (Vietnam Journal of Community Medicine, 2025)
Objective: The aim of this study was to determine the prevalence of anemia in pediatric patients with chronic kidney disease (CKD) stages G3a-5 at the Nephrology-Endocrinology Department, Children's Hospital 2 (CH2) in 2025, and to investigate the factors associated with anemia.Subjects and methods: This cross-sectional study was conducted with 77 pediatric patients diagnosed with CKD stages G3a to G5, aged over 2 years, receiving outpatient or inpatient care at CH2 in 2025. Anemia and nutritional status were classified according to the World Health Organization (WHO) standards. The association between anemia and demographic, disease-related, and nutritional factors was also explored.Results: The prevalence of anemia in the study population was 77.9%, with 52% of cases exhibiting moderate anemia. Normocytic, normochromic anemia was present in 75% of cases. Approximately 40% of the patients had iron deficiency. Statistical analysis revealed a significant association between anemia and the patient's age group (OR = 1.26; 95% CI: 1.04 – 1.52), disease stage (PR = 1.66; 95% CI: 0.93 – 2.95), treatment method, and chronic malnutrition status (PR = 1.36; 95% CI: 1 – 1.86).Conclusion: The prevalence of anemia in pediatric patients with CKD stages G3a-5 is high at 77.9%, with more than 50% of cases being classified as moderate anemia, and the majority being normocytic, normochromic. There is a need to enhance collaboration between nephrologists and nutrition specialists in adjusting dietary interventions to more effectively manage anemia in this group of pediatric CKD patients.
Keywords: chronic kidney disease, anemia, children, diet.